Localization and Topography of the Arteries on the Middle Forehead Region for Eluding Complications Following Forehead Augmentation: Conventional Cadaveric Dissection and Ultrasonography Investigation. Issue 7 (October 2020) - Phumyoo, Thirawass; Jiirasutat, Nuttapatch; Jitaree, Benrita; Rungsawang, Chalermquan; Pratoomthai, Benjamart; Tansatit, Tanvaa
Abstract : Abstract: Forehead augmentation with filler injection is one of the most dangerous procedures associated with iatrogenic intravascular injection resulting in the severe complications. Nonetheless, few studies have determined the explicit arterial localization and topography related to the facial soft tissues and landmarks. Therefore, this study aimed to determine an arterial distribution and topography on the middle forehead region correlated with facial landmarks to grant an appropriate guideline for enhancing the safety of injection. Nineteen Thai embalmed cadavers were discovered with conventional dissection and 14 Thai healthy volunteers were investigated with ultrasonographic examination on the middle forehead. This study found that at the level of mid-frontal depression point, the transverse distance from the medial canthal vertical line to the superficial and deep branches of supraorbital artery were 9.1 mm and 15.1 mm, respectively. Whereas the depths from the skin of these arteries were 4.1 mm and 4.3 mm, respectively. Furthermore, the frontal branch of superficial temporal artery was detectable in 42.1% as an artery entering the forehead area. At the level of lateral canthal vertical line, the vertical distance of frontal branch was 31.6 mm, and the depth from skin of the artery was 2.7 mm. In conclusion, a proper injection technique could be performed based on an intensive arterial distribution and topography, and ultrasonographic examination before the injection is also suggested in order to restrict the opportunity of severe complications. Abstract : Supplemental Digital Content is available in the text